Escape the Womb: A Maternal Emergency. (February 2021) - Hardie, Lori; Gill, Amanda; Lee, Stephanie; Shiveley, Jody
Background: Due to advanced maternal age, obesity, drug use, and other comorbidities, the frequency ofmaternal cardiac arrest continues to rise nationally and in our Midwestern community hospital. While still a relatively rare occurrence, the national rise inmaternal mortality rates has created a need for population-specific resuscitation education for caregivers ofobstetric patients . Educators are challenged with creating engaging, meaningful education that is inexpensive and effective. Educationalescape rooms challenge participants to discover clues, solve puzzles, progress through the game and ultimately escape the room. The format offers team problem-solving andexperiential learning with immediate feedback in an enjoyable atmosphere. Aim: In order to provide aninterprofessional and economical educational intervention for labor and delivery teams, the authors created anescape room focused on principles of effectivematernal resuscitation . Method: Participants completed an evaluation tool measuring perceptions of content clarity and confidence, and an author created pre-test and post-test to measure knowledge of cardiopulmonary resuscitation medications and interventions for the obstetric patient. Results and Conclusions: Comparison of aggregated pre- and post-test showed an 11% increase in knowledge scores. All participants self-evaluation showed improved clarity and confidence and described the activity as a fun way to learn and reinforce knowledge.